Caries risk and preventive home-treatment in pre-school children - An Irene Donuts ellaborative pilot study - Suwargiani, Anne Agustina; Wardani, Riana; Putri, Fidya Meditia; Susilawati, Sri; Zubaedah, Cucu; Jasrin, Tadeus Arufan (Universitas Padjadjaran, 2018)
Introduction: Caries risk assessment is an effort performed to determine the causes of dental caries and the caries risk of the children. The purpose of the study was to determine the caries risk of pre-school children and the possible preventive home-treatment in reducing the risk. Methods: This research was descriptive with sampling method used was the total sampling technique. Data were collected using the Irene’s Donuts caries risk form to determine the caries risk and preventive treatment of the children. Caries risk assessment data was presented in the form of frequency distribution tables. Results: The first-year research resulted as follows: distribution of caries risk frequency based on the interview conducted towards the parents in Ulul Azmi and Amanah Kindergarten, regarding their education, age, children’s habits, showed that the highest risk (88.9%) in both kindergartens was found in children who still drink milk with pacifier bottles until more than four-years-old. The second highest risk amongst Ulul Azmi Kindergarten students (88.9%) was found in children with daily candy consumption; the highest risk amongst Arroyyan Kindergarten (90%) was tooth decay which considered not interfering the children’s development with the pH level below 6.5. Regarding the treatment choice of the students, the most choices taken amongst Ulul Azmi Kindergarten parents were helping their children brush their teeth at night before bedtime; assuring the children’s sufficient water consumption in Amanah Kindergarten parents; assuring the children’s vegetable and fruits contained menu in Arroyyan Kindergarten parents. Conclusion: The highest caries risk of pre-school children is tooth decay, with the possible preventive home-treatment, were helping the children to brush their teeth at night before bedtime, assuring the children’s sufficient water consumption, and assuring the children’s vegetable and fruits contained menu.